The Disharmonization of Wills Decisions by Judges on the Basis of Justice Values - Miftakhudin, Muh. (Jurnal Konstatering, 2022)
The purpose of writing is to find out and analyze: (1) the disharmony of legal decisions against wills by courts; (2) the position of the will deed in inheritance law in Indonesia. The approach used in this paper is normative juridical. Research specifications using analytical descriptive are strengthened by perspective. Sources of research data are sourced from primary legal materials, secondary legal materials and tertiary legal materials. Techniques for collecting legal materials using document or literature studies. The legal material analysis technique uses normative qualitative. The results of the study concluded that: (1) Disharmonization that occurred in the legal decision regarding a will by a panel of judges between levels of the judiciary, because the content of the judge's decision was different. The judge's decision has the potential to violate the legitieme portie, because on the land that was bequeathed only to his two children, a hotel business was built which was inherited by all his children; (2) The status of wills in inheritance law in Indonesia, namely: (a) according to the Civil Code and Islamic Compilation Law (HKI), the heir can make a will both to his heirs (grant/legaat will) and other people (will to appoint heirs) /erfstelling); (b) The testamentary deed is effective in the process of transferring inheritance after the testator dies; (c) a will made before a Notary is an authentic deed and has 3 (three) evidentiary powers before a court; namely: physical evidentiary power (uitwendige bewijskracht), formal evidentiary power (formele bewijskracht) and material evidentiary power (materiele bewijskracht).Keywords: Disharmony; Justice; Wills.